Rational construction of an ssa-type of MOF through pre-organizing the ligand's conformation and its exceptional gas adsorption properties. Issue 7 (31st January 2018) - Wang, Yao; He, Minghui; Tian, Zhi; Zhong, Haoyan; Zhu, Lisha; Zhang, Yingying; Zhang, Xiaoping; Chen, De-Li; He, Yabing
Abstract : A ligand conformation-controlled assembly strategy has been successfully employed to construct a copper-based MOF with the desired ssa -type topology, which exhibits exceptional C2 H2 and CO2 adsorption properties. Abstract : Ssa -type MOFs constructed from dicopper paddlewheels and bent diisophthalate ligands exhibit a promising potential for gas adsorption which benefits from their rich open copper sites and polyhedron-based cages with suitable sizes. However, the rational construction of such types of MOFs is exceedingly challenging because the bent diisophthalate ligands employed are inclined to exhibit various conformations and thus are prone to form MOFs with varied topologies. In this work, by pre-organizing the ligand's conformation, we successfully targeted an ssa -type MOFZJNU-57 from a bent diisophthalate ligand. More significantly, ZJNU-57 exhibits excellent hydrolytic stability and high C2 H2 and CO2 uptake capacities as well as impressive C2 H2 /CH4 and CO2 /CH4 adsorption selectivities, indicating its promising potential for C2 H2 /CH4 and CO2 /CH4 separation, which are relevant to acetylene production and natural gas purification. This work not only provides a rare water-stable MOF based on the Cu2 (COO)4 cluster for highly selective adsorption of C2 H2 and CO2 from CH4, but also demonstrates that the ligand conformation-controlled assembly strategy may be an efficient approach toward the construction of MOF materials with definite topologies for specific applications.